2018
DOI: 10.1103/physreve.97.052211
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic nonreciprocity in a lattice incorporating nonlinearity, asymmetry, and internal scale hierarchy: Experimental study

Abstract: In linear time-invariant systems acoustic reciprocity holds by the Onsager-Casimir principle of microscopic reversibility, and it can be broken only by odd external biases, nonlinearities, or time-dependent properties. Recently it was shown that one-dimensional lattices composed of a finite number of identical nonlinear cells with internal scale hierarchy and asymmetry exhibit nonreciprocity both locally and globally. Considering a single cell composed of a large scale nonlinearly coupled to a small scale, loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Topological states have been successfully observed in several platforms [13][14][15][16][17][18][19][20][21], and have been pursued to achieve robust, diffraction-free wave motion. Additional functionalities have been explored in the context of topological pumping [22][23][24][25][26], quasi-periodicity [27][28][29], and non-reciprocal wave propagation in active [30][31][32][33][34][35][36] or passive non-linear [37][38][39][40] systems. These works and the references therein illustrate a wealth of strategies for the manipulation of elastic and acoustic waves, and suggest intriguing possibilities for technological applications in acoustic devices, sensing, energy harvesting, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Topological states have been successfully observed in several platforms [13][14][15][16][17][18][19][20][21], and have been pursued to achieve robust, diffraction-free wave motion. Additional functionalities have been explored in the context of topological pumping [22][23][24][25][26], quasi-periodicity [27][28][29], and non-reciprocal wave propagation in active [30][31][32][33][34][35][36] or passive non-linear [37][38][39][40] systems. These works and the references therein illustrate a wealth of strategies for the manipulation of elastic and acoustic waves, and suggest intriguing possibilities for technological applications in acoustic devices, sensing, energy harvesting, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the stiffness of the bilinear spring is greater in compression than in tension, we set ∆ j,c > ∆ j,t = 0 and ∆ j,c changes linearly over location according to Eqs. (8) and (9) . Figures 14(a) and 14(b) depict the displacement fields along the test chain at four different moments for the stiffness modulations of Fig.…”
Section: Spatial Modulation Of the Bilinear Stiffnessmentioning
confidence: 99%
“…The same incident wave traveling in opposite directions should result in the same transmitted wave. Recent advances have shown that the principle of reciprocity can be violated under special conditions in electromagnetism [1], acoustics [2,3,4,5,6,7,8,9,10] and other physical systems supporting wave propagation [11]. The ability to violate reciprocity in a controlled and passive manner opens the possibility of extreme wave dynamics and control mechanisms such as one-way propagation, acoustic diodes, etc, and provide revolutionary solutions to existing problems and useful tools for promising applications.…”
Section: Introductionmentioning
confidence: 99%
“…One way to realize acoustic non-reciprocity is by applying a bias that is oddly-symmetric upon time reversal, which has been achieved in moving media [6,7], gyroscopic phononic crystals [8,9], and piezophononic media [10], for example, and effectively establishes 'up-stream' and 'down-stream' directions for propagating waves. Another means to break reciprocity is nonlinearity, which has been used to create one-way sound propagation via harmonic generation [11][12][13]. A third mechanism, which is the subject of the present study, is spatiotemporal modulation of material properties [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 97%